Maximum Number of Line Faults in a P2P Network System Based on the Addition-Min Fuzzy Relation Inequalities - Yang, Xiao-Peng; Zheng, Gengzhong (IEEE transactions on fuzzy systems, 2022)
The addition-min fuzzy relation inequalities could be applied to characterize the peer-to-peer (P2P) network system. This article focuses on the problem that how many arbitrary (or specific) line faults a P2P network system is able to bear at most. In order to find the maximum number of tolerant line faults, we first study the consistency checking of the P2P network system with a given number of arbitrary line faults. Corresponding properties and illustrative example are also presented. Furthermore, the so-called reordered-vector-based (RVB) algorithms I and II are proposed for searching the maximum number of arbitrary and specific line faults in a given P2P network system, respectively. The validness of our proposed RVB algorithms is verified by formally proving and some numerical examples.